Evaluation of lobar lymph node metastasis in non-small cell lung carcinoma using modified total lesion glycolysis - Dejima, Hitoshi; Kuroda, Hiroaki; Oya, Yuko; Sakakura, Noriaki; Inaba, Yoshitaka; Tamaki, Tsuneo; Yatabe, Yasushi; Sakao, Yukinori (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: Volumetric parameters based on 3-dimensional reconstruction have recently been introduced for cancer staging. We aimed to improve the ability to diagnose hilar lymph node metastasis in patients with non-small cell lung cancer. Methods: We evaluated 142 patients with non-small cell lung cancer who underwent right upper lobectomy and radical lymph node dissection. Metastatic involvement of right upper lobar lymph nodes was assessed using high-resolution computed tomography (HRCT) and 18F-2-floro-2-deoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT). Results: On receiver operating characteristic (ROC) curve analysis, the area under the curves (AUC) for short axis, maximum of standardized uptake value (SUVmax), total lesion glycolysis (TLG) and modified TLG (mTLG) were 0.79, 0.77, 0.76, and 0.87, respectively. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of mTLG, using the optimal cut off value (2.45), for diagnosis of lobar lymph node metastasis were 71%, 88%, 44%, and 96%, respectively. Hilar asymmetric uptake (HAU) of FDG was larger in true-positive cases than in false-negative cases (P